Model Scrum pada Rekacipta Sistem Informasi Manajemen Program Kerja dan Anggaran di Pusat Pengembangan Anak - Cahyono, Ariya Dwika; Haryani, Endang (STIKOM Tunas Bangsa Pematangsiantar, 2024)
This research aims to create a web-based management information system of work program and budget in the Child Development Center (CDC) as a management tool of planning and controlling. This research was conducted due to problems caused by manual management with spreadsheets and desktop-based applications, as well as manual and separate management between planning and realization. The development of this web-based application applies the Scrum model, which consists of 7 sprints. This Scrum model has organized system development in detail and according to user needs. After completing the research stages, this system was successfully developed. This application can facilitate adminitrators of work program and budget to work effectively and efficiently. Adminitrators can work anywhere and anytime. The automation process in the system guarantees the accuracy of calculations and adequate management. Thus, CDC's need for a basic infrastructure, namely management information systems of work program and budget, has been achieved. This system is an important benchmarking for CDCs, since the same procedure applies on all CDCs in Indonesia.